Multiple Calvarial Lytic Lesions: A Differential Diagnosis from Early Medieval France (5th to 7th c. AD). (5th July 2012) - Bauduer, F.; Bessou, M.; Guyomarc'h, P.; Mercier, C.; Castex, D.
ABSTRACT A skull from the early French Medieval period presenting multiple destructive lesions is investigated. The study of this presumably young female skull suggests a series of possible diagnoses using macroscopic features, standard radiography, CT, and 3D analysis. After a review of the paleopathological and medical literature, the debate focuses on several malignant disorders (cancerous metastases, multiple myeloma), Langerhans cell histiocytosis, and other benign conditions such as infection (especially tuberculosis) or sarcoidosis. Although the definite diagnosis of such paleopathological lesions is not straightforward, Langerhans cell histiocytosis is the most probable diagnosis. Copyright © 2012 John Wiley & Sons, Ltd.